Investigation of electrochemical properties of homemade nano gold electrodes and application in determination of Hg(II) at the trace levels - Hai Yen, Pham Thi; Thu Ha, Vu Thi; Duy, Pham Khac; Dang, Vu Hai (Vietnam Journal of Chemistry, 2015)
The electrochemical properties of two nanoscale electrodes: Au nanodendrite and nanopartiles fabricated on Pt substrate disk have been studied. The initial results showed that the electrodes have a good electrochemical behavious. Using DPASV techniques with pulse height 50 mV, pulse width 40 ms, it is possible to determine amount of Hg(II) in water until ppb levels. Due to larger active area with porous structure, Au-ND/Pt can be used to detect a smaller amount of Hg(II) in water compared to Au-NPs/Pt. Detection limits found in these two cases is  0.081 ppb and 0.037 ppb for Au-NPs/Pt and Au-ND/Pt respectively and these electrodes are applicable to directly detect Hg(II) in water environment. Keywords. Gold nanodendrite, gold nanopartilces, mercury detection, trace level